The Effectiveness of Affective and Social Strategies to Teach Speaking for Students with High and Low self Confidence - Shofwani, Siti Aniqoh; Faridi, Abdurrahman; Anggani Linggar Bharati, Dwi (English Education Journal, 2019)
The English subject in formal school becomes one of the important material in Indonesia. The purpose of learning a foreign language here is; to make the students be able to communicate in using English not only in written form but also orally. This research is quantitative, where the findings are presenting in the graphic and diagram with the calculation of results. The findings show, there are pre-test, materials delivering and post-test into two class. It shows in the pre-test, IPS I is better than IPS II, it can be seen by the score and the performance in the video. During the pre-test, IPS I is more variety in uttering the language, they can enhance the utterances although it still not be perfect. Treatment is done after pre-test, in this activity, the researcher gives materials in greeting, how to make good utterances and how to enhance the utterances during speaking so that the time while the test can be more efficient. After that, in post-test activity, IPS I is still dominant in a better score and perform better because they can use phatic and enhance their utterances and make their time test more efficient. Finally, that research has the suggestion for the teacher in teaching speaking if using social and affective strategies are effective to develop the ability of the students in oral language.